(3cTGa EUWdGMGJ Gdafhf hGdYdhes - (3eMeO Ydj Hf Ydj Hf bGVj eMeO MGeO GdJgGfhj GdgfOjs
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdEfSGf hYdeg GdHjGf hHYO jbhd GdYHO GdVYja Ef CcKQ eG jMJGL Hg ai JMUjd GdYdhe GdeOhfI hGdafhf GdeRhLI Edi GdCSGJPI gh CTHGg GdEUWdGM aEf dcd Yde EUWdGM NGU Hg s
(3BNQgG (B:s
(3hYfO Cgd GdMbjbI gh GdEeSGc CeG GdUhe aETGQI Edi GdEeJfGY Yf ESJYeGd ebJVjGJ GdHTQjI ebJVH HUaGJ GdYeOjI aYdi bOQ s
(3GdejcQhajde Je JbSjeg Ydi YdHJjf (B( (3C (B, (3H (B) (3hgPG gh GdYdHI Cs
(3GdfSNI HgG MhGTs
(3HChdgG ahGFO YHGQI Yf JaSjQ GdLRA ef ShQI GdUGaGJ s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdeYGQa GdYGeIs